The Influence of Motivation, Compensation, and Participatory Leadership Styles on Employee Performance at PT. Kusuma Raya Utama of Central Bengkulu - Muhammad Abdi Pratama; Ida Anggraini; Yesi Indian Ariska (Jurnal Fokus Manajemen, 2021)
The aim of this study is to determine the influence of work motivation, compensation and participatory leadership style on employee performance at PT Kusuma Raya Utama of Central Bengkulu. The sampling method using saturated sampling is a sampling technique when all members of the population are used as samples. The analysis method uses multiple linear regression analysis and its components are processed by the SPSS program.The results showed that motivation, compensation and participatory leadership style had a positive and significant influence on employee performance at PT. Kusuma Raya Utama of Central Bengkulu which indicated the coefficient value of the three independent variables (X) was positive and the value of sig. 0.000 is below 0.05 (0.000<0.05), so the value of Fcount is greater than Ftable (1257.621>2.71). Motivation has a positive and significant influence on employee performance which is indicated by the positive motivation coefficient and the sig value. 0.000 is below 0.05 (0.000<0.05), so the value of t countis greater than t table (2.678>1.66277). Compensation has a positive and significant influence on employee performance which is indicated by a positive compensation coefficient and a sig value. 0.009 is below 0.05 (0.009<0.05), so the value of tcount is greater than t table (9.143>1.66277). Participatory leadership style has a positive and significant influence on employee performance which is indicated by the coefficient value of the positive participatory leadership style and the sig value. 0.000 is below 0.005 (0.000 <0.005), so the value of t count is greater than t table (2.678>1.66277)..